Case WX 150 excavator engine common rail application of fuel supply system - Ostonov Shukhrat Saidovich; Makhmudova Maftuna Makhsud qizi; Kerimov Ruslan Zakirovich; Ergashev Saidolim Inomjon ugli; Sobirov Komil Sodiq uglu (Global Scientific Publishing, 2022)
This article shows that the performance of a car engine depends on factors such as optimal fuel consumption, low emissions, full power transfer to the required units. Keeping the engine in good condition depends on the accuracy and reliability of the materials used in the engine during production, and in the process of its use depends on the quality of maintenance
Keywords: Car,; engine; fuel; gasoline